Cobalt single atom catalysts for the efficient electrosynthesis of hydrogen peroxide. Issue 11 (21st April 2021) - Xu, Hui; Zhang, Shengbo; Geng, Jing; Wang, Guozhong; Zhang, Haimin
Abstract : Cobalt single atoms anchored on N-doped graphitic carbon were successfully synthesised and exhibited superior two-electron oxygen reduction reaction activity with a H2 O2 selectivity of ∼76.0% at 0.5 V ( vs. RHE). Abstract : We report the synthesis of cobalt (Co) single atoms (SAs) anchored on N-doped graphitic carbon (Co-SAs/NC) by the pyrolysis of a mixture of cobalt chloride hexahydrate, ethylene diamine tetraacetic acid (EDTA) and polyvinylpyrrolidone (PVP). As an electrocatalyst, the Co-SAs/NC with a surface area of 165.6 m 2 g −1 and a dominant mesoporous structure exhibited superior two-electron oxygen reduction reaction (2e − ORR) activity in 0.1 M KOH electrolyte, affording a very positive onset potential of 0.84 V ( vs. RHE) and a H2 O2 selectivity of ∼76.0% at 0.5 V ( vs. RHE). The long-term durability tests indicated that the Co-SAs/NC can generate 380.9 ± 14.85 μmol H2 O2 stably after 10 h of reaction at 0.5 V ( vs. RHE) in 0.1 M KOH, showing only ∼10% decay of the current and the corresponding faradaic efficiency (FE) of ∼72.1 ± 4.2%. The superior 2e − ORR performance of Co-SAs/NC is ascribed to the synergetic effect of the Co–N x active sites and nearby oxygen functional groups.